CÂMBIO, INFLAÇÃO, JUROS E RESERVAS NA TRANSIÇÃO DE REGIMES CAMBIAIS: UMA INVESTIGAÇÃO ECONOMÉTRICA PARA O BRASIL - Vieira, Flávio Vilela (2009)
The present paper examines the exchange regime transition in Brazil estimating a VAR model and its instruments. The main initial hypothesis is that there were significant changes in the relation among exchange rate, interest rate, inflation and international reserves. It also examines if the fear of floating is justifiable. The empirical findings suggest the occurrence of such changes when switching from a more rigid to a flexible exchange regime, which corroborates our initial hypothesis. Summarizing the empirical results we can argue that when comparing the two exchange rate regimes there is a similarity in terms of exogeneity of the exchange rate, the relevance of the interest rate for inflation stabilization (demand restriction) for the rigid exchange rate regime and how the interest rate responds to inflation (inflation target) in the flexible regime. Regarding the fear of floating the results do not match the others from the literature for other economies under exchange regime transition and the credibility does not seem to be a problem when such transition to a more flexible regime is adopted.